Bacterial Vaginosis and Alcohol Consumption: A Cross-Sectional Retrospective Study in Baltimore, Maryland. Issue 12 (14th December 2021) - Froehle, Leah; Ghanem, Khalil G.; Page, Kathleen; Hutton, Heidi E.; Chander, Geetanjali; Hamill, Matthew M.; Gilliams, Elizabeth; Tuddenham, Susan
Abstract : A study of women attending sexually transmitted infection clinics in Baltimore, MD, found a significant positive association between at-risk alcohol use and bacterial vaginosis. Supplemental digital content is available in the text. Abstract : Background: Bacterial vaginosis (BV) is the most cited cause of vaginal complaints among women of reproductive age. Its etiology and associated risk factors are not entirely understood. Here we examined the association between BV and at-risk alcohol consumption in women attending 2 sexually transmitted infection (STI) clinics in Baltimore, MD. Methods: This was a retrospective cross-sectional analysis using data from first clinic visits from 2011–2016. At-risk alcohol use was defined as heavy episodic ("binge") drinking within the last 30 days or a self-report of having had vaginal or anal sex in the context of alcohol consumption. Pearson χ 2 test and Student t test were used to assess baseline associations. Log binomial models were used to estimate prevalence ratios (PRs) before and after adjustments for potential confounding factors. Results: Of the 10, 991 women included in the analysis, 2173 (19.7%) met the clinical diagnostic criteria for BV. Having had vaginal or anal sex in the context of alcohol consumption was associated with an increased risk of BV (PR, 1.25; 95% confidence interval, 1.13–1.37), as was binge drinking (PR, 1.15; 95% confidence interval, 1.04–1.27) after adjustment for confounders. Conclusions: In this population, at-risk alcohol consumption was associated with an increased risk of BV. The mechanisms remain uncertain. Future prospective studies are needed to verify and evaluate causality in these associations.